Psychometric properties of developed and transadapted grit measures across cultures: a systematic review - Abu Hasan, Hezne Ezaty; Munawar, Khadeeja; Abdul Khaiyom, Jamilah Hanum (Springer, 2020)
A growing interest in grit, which is defined as passionate perseverance for long-term goals, has included interest in quantifying it. Grit is typically measured via a self-report questionnaire, either with the Original Grit Scale (Grit-O) or the Short Grit Scale (Grit-S). However, there is a paucity of systematic evidence of the psychometrics of translated and adapted, or transadapted, versions of the grit measures across settings. This study systematically reviewed the literature on the psychometric properties of grit measures available and used across cultures. We searched the PsycINFO, Scopus, ScienceDirect and ProQuest electronic databases for articles published in English up to October 2019. This review was conducted following the PRISMA guidelines. A total of 20 studies met the inclusion criteria, which included eight studies on newly developed grit measures and 12 studies which transadapted the existing Grit-O and the Grit-S to various languages and contexts. In the first category, despite being newly developed, the grit measures included items that were derived from the Grit-O or the Grit-S. These measures show promise, however, remain to be tested outside of the initial conception setting, thus limiting generalization. In the latter category, transadapted versions of the Grit-O and Grit-S returned with acceptable reliability and validity indexes, indicating for the measures to purportedly measure grit. However, factor analyses showed varying factor structures, suggesting grit manifestations to be non-universal and may be explained by cultural differences between individualistic and collectivistic cultures. Further validation studies, as well as the development of culture-specific grit measures, are implored.